Principles of Political Economy - Saros, Daniel E.; Open Textbook Library (Open Textbook Library, 2019)
This textbook is unique among economics textbooks. It contains many of the same topics as mainstream textbooks, but it includes and takes very seriously heterodox critiques and alternatives to the mainstream approach to economics. It includes a whole range of alternative theories, including Post-Keynesian, Austrian, Marxian, radical, feminist, institutionalist, and other approaches. The purpose is to teach students about alternative schools of economic thought but also to deepen their understanding of the dominant, neoclassical approach to economics. In this sense, it draws a great deal of inspiration from Richard Wolff and Stephen Resnick's Contending Economic Theories. Following Wolff and Resnick, an even broader objective is to teach students that economics is a discourse and that no single voice can rightfully claim to have a monopoly on the truth about economics.
I. Part One: An Introduction to Economic Theory -- II. Part Two: Principles of Microeconomic Theory -- III. Part Three: Principles of Macroeconomic Theory -- IV. Part Four: Principles of International Economic Theory
In English.
Description based on print resource
Keywords: Economics -- Textbooks; Political Science -- Textbooks